Indirect exposure to novel coronavirus (SARS-CoV-2): an overview of current knowledge - Enyoh, Christian Ebere; Wirnkor Verla, Andrew; Qingyue, Wang; Kumar Yadav, Dipak; Akhter Hossain Chowdhury, Md; Obinna Isiuku, Beniah; Chowdhury, Tanzin; Chizoruo Ibe, Francis; Ngozi Verla, Evelyn; Oluwatosin Maduka, Tochukwu (Jurnal Teknologi Laboratorium, 2020)
This review chronicles the indirect transmission method which seems to be overlooked by most people and makes attempts to document the various transmission ways with a hope that such information may strengthen the knowledge base of researchers towards methods of eradicating the pandemic. Current knowledge of transmission and exposure of SARS-CoV-2 has been explained. Various researchers have put forward different ways of exposure and transmission. Literature does not reveal whether the indirect transmission route is the dominant one. However, total lockdown could be a veritable means to reduce both direct and indirect transmission routes. In many countries where the indirect transmission has been reduced, the scourge of the virus is less. The work creates awareness on the need to watch out for those routes of transmissions that may not be popular and suggested vital knowledge gaps that need to fill.